Routine prophylactic application of Monsel's solution after loop electrosurgical excision procedure of the cervix: Is it necessary? - Kietpeerakool C. (2014)
Aim: To determine the benefit of an immediate application of Monsel's solution after loop electrosurgical excision procedure (LEEP) of the cervix for preventing postoperative bleeding. Methods: This randomized controlled trial was conducted at Chiang Mai University Hospital, Chang Mai, Thailand. Women who were scheduled for LEEP were approached for participation in the study. The primary endpoint was the duration of uncomplicated vaginal bleeding. Secondary endpoints were the incidence of persistent vaginal bleeding, and postoperative complications including severe early bleeding, severe delayed bleeding and infection. Results: Between October 2004 and May 2006, 285 women with an abnormal Pap-smear, who had undergone LEEP, were randomly allocated to the Monsel's group (n = 140) or control group (n = 145). The baseline outcomes were similar between the two groups. In the Monsel's group, the duration of uncomplicated vaginal bleeding was significantly shorter (P < 0.001) and the occurrence of persistent vaginal bleeding was significantly lower (P = 0.014) than in the control group. The occurrence of severe complications that required treatment, including bleeding and infection, was not significantly different between the two groups (P = 0.379). Conclusion: An application of Monsel's solution after LEEP appears to reduce the duration of postoperative vaginal bleeding, but does not significantly prevent severe complications. Such practice may not be necessary if adequate hemostasis is achieved using electrical cauterization. © 2007 The Authors.